Scientific substantination of maximum allowable concentration of fluopicolide in water - Pelo I.М.; Blagaia A.V. (Medičnì Perspektivi)
In order to substantiate fluopicolide maximum allowable concentration in the water of water reservoirs the research was carried out. Methods of study: laboratory hygienic experiment using organoleptic and sanitary-chemical, sanitary-toxicological, sanitary-microbiological and mathematical methods. The results of fluopicolide influence on organoleptic properties of water, sanitary regimen of reservoirs for household purposes were given and its subthreshold concentration in water by sanitary and toxicological hazard index was calculated. The threshold concentration of the substance by the main hazard criteria was established, the maximum allowable concentration in water was substantiated. The studies led to the following conclusions: fluopicolide threshold concentration in water by organoleptic hazard index (limiting criterion – the smell) – 0.15 mg/dm3, general sanitary hazard index (limiting criteria – impact on the number of saprophytic microflora, biochemical oxygen demand and nitrification) – 0.015 mg/dm3, the maximum noneffective concentration – 0.14 mg/dm3, the maximum allowable concentration - 0.015 mg/dm3.